Operation at Tridewinds plantation / Safwan Yusri and Muhammad Aliuddin - Yusri, Safwan; Aliuddin, Muhammad (Faculty of Plantation and Agrotechnology, 2018)
Farm mechanization in Tradewinds plantation was used to minimize the labor. In Tradewinds plantation have 3000-hectare area oil palm. A survey using the secondary data last 4 years ago to know the total cost of operation on oil palm plantation. According a survey for the total cost was including the fixed cost and operation cost for get the total cost of operation at plantation. To identified the operation cost that was including the fuel cost and maintenance cost that affect the total cost of operation. The data what was collected try to identify factor of increasing the total cost for operation. The main factor of total cost is maintenance cost that effect the total cost of operation. All data was use the Microsoft Excel to list down all cost including in operation cost For the operation cost was calculate the deprecation, tax. shelter and insurance. Based on analysis previous four years of total cost in year 2017 is RM 38,680.03 are higher compare another year The lower total cost in year 2015 is RAI 29.835.20 are the low er cost of operation in plantation. However, all the total cost have factor that effect the higher and lower total cost of operation such as the maintance and repair cost.